Advanced Experimenting on Wave Interaction with Low-Crested Breakwaters - Neves, A; Gomes, F; Pinto, F (The International Journal of Multiphysics, 2010)
Two-dimensional scaled physical tests were carried out in the Hydraulics Laboratory wave tank of the University of Porto in order to more accurately understand the effect of submerged breakwaters on wave-induced velocities and pressure fields. The slow-varying pressures acting normally on the slope were simultaneously measured with the flow-induced velocities at the surface, and an analysis of their distribution along the whole structure-on the front slopes, rear slopes and along the crown-was done as this information is considered potentially useful for hydraulic design. Different points on the breakwater model were considered and diverse wave conditions were tested, allowing study of the dependency of pressures/velocities on model characteristics. Maximum, minimum and mean phase-averaged values of these variables were calculated, allowing the detection of potentially sensitive areas in terms of pressure and velocities at the surface. A spectral analysis of these physical variables was also perfomed in order to check the results obtained with the regular wave tests.